2021
DOI: 10.3390/v13122433
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of Co-Infection and Trans-Encapsidation of Viral RNA In Vitro Using Epitope-Tagged Foot-and-Mouth Disease Viruses

Abstract: Foot-and-mouth disease, caused by foot-and-mouth disease virus (FMDV), is an economically devastating disease affecting several important livestock species. FMDV is antigenically diverse and exists as seven serotypes comprised of many strains which are poorly cross-neutralised by antibodies induced by infection or vaccination. Co-infection and recombination are important drivers of antigenic diversity, especially in regions where several serotypes co-circulate at high prevalence, and therefore experimental sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…Nevertheless, that finding suggests that packaging an interserotypic recombinant FMDV genome into an FMDV-O capsid does not incur a fitness loss. This is consistent with a recent investigation of cell culture coinfection which demonstrated trans-encapsidation of serotypes FMDV-Asia 1 and FMDV-O genomes in heterologous capsids [34].…”
Section: Discussionsupporting
confidence: 92%
“…Nevertheless, that finding suggests that packaging an interserotypic recombinant FMDV genome into an FMDV-O capsid does not incur a fitness loss. This is consistent with a recent investigation of cell culture coinfection which demonstrated trans-encapsidation of serotypes FMDV-Asia 1 and FMDV-O genomes in heterologous capsids [34].…”
Section: Discussionsupporting
confidence: 92%
“…We recently showed that the co-infection of cells with two different FMDV viruses can be studied in vitro using viruses with epitope tags in their VP1 capsid proteins [18]. These experiments showed for the first time that co-infection can result in the trans-encapsidation of FMDV genomes, and that chimeric FMDV capsids containing protein subunits from both parental viruses can be generated.…”
Section: Discussionmentioning
confidence: 99%
“…The extent to which this can happen between serotypes is unclear due to the requirement for functional compatibility between subunits in the capsid, but it may be more likely to occur between different strains within the same serotype. Recently, we used recombinant serotype O FMDVs containing either an HA or a FLAG epitope tag in the VP1 capsid protein to demonstrate that, in co-infected cells, HA-VP1 and FLAG-VP1 proteins could assemble into the same capsid [18]. In theory, a capsid containing two different VP1 proteins may be less sensitive to neutralization by antisera against either one of the parental viruses.…”
Section: Introductionmentioning
confidence: 99%